Planejar para contar: percursos na formação dos leitores literários no CELLIJ - Zocolaro, Isabela Delli Colli [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
As a requirement of the Pedagogy course of the Faculty of Science and Technology at UNESP, the Course Conclusion Paper - TO PLAN TO TELL: PATHS IN THE TRAINING OF LITERARY READERS AT CELLIJ - considers the relevance of the practice of storytelling, especially for children , and its significance as art, this investigation seeks to show, through a bibliographical research, the importance of planning the moments of telling, carefully thinking about the story and the techniques, elements and gestures that will be used in the narrative, so that the listener has a pleasurable experience with history and literature. Thus, this objective is achieved through the bibliography used and the reports of experiences at CELLIJ (Center for Studies in Reading and Literature for Children and Youth) “Maria Betty Coelho Silva” of the São Paulo State University “Júlio de Mesquita Filho”, Campus of Presidente Prudente, space that offers storytelling that are previously planned so that all the details aim to offer a wonderful experience with the story, and contribute to the formation of literary readers. This way, in the light of authors such as Girotto and Souza (2010), Busatto (2003), Sisto and Motoyama (2016), Garcia (2007), Silva (1986) and others, this work permeates the art of storytelling, storytelling strategies, reading, mediation. Themes that shows the importance of this ancient practice, bringing ways to make it more meaningful, and its possibilities to train readers.

Como exigência do curso de Pedagogia, da Faculdade de Ciências e Tecnologia da UNESP, o Trabalho de Conclusão de Curso - PLANEJAR PARA CONTAR: PERCURSOS NA FORMAÇÃO DOS LEITORES LITERÁRIOS NO CELLIJ - considera a relevância da prática da contação de histórias, principalmente para as crianças, e sua significância como arte, esta investigação busca mostrar, através de uma pesquisa bibliográfica, a importância de se planejar os momentos de contação, pensando cuidadosamente na história e nas técnicas, elementos e gestos que serão utilizados na narrativa, para que o ouvinte tenha uma experiência prazerosa com a história e a literatura. Assim, este objetivo é alcançado através da bibliografia utilizada e dos relatos de experiências no CELLIJ (Centro de Estudos em Leitura e Literatura Infantil e Juvenil) “Maria Betty Coelho Silva” da Universidade Estadual Paulista “Júlio de Mesquita Filho”, Campus de Presidente Prudente, espaço que oferece contação de histórias que são planejadas anteriormente de modo que todos os detalhes visam oferecer uma experiência de maravilha com a história, e contribuir para a formação de leitores literários. Desse modo, à luz de autores como Girotto e Souza (2010), Busatto (2003), Sisto e Motoyama (2016), Garcia (2007), Silva (1986) e outros, este trabalho perpassa pela arte de contar histórias, estratégias de leitura, mediação, temas que constroem a importância dessa prática milenar, trazendo meios de torna-la mais significativa, e suas possibilidades de formar leitores.
Plan to tell: paths for the formation of literary readers in CELLIJ
Keywords: Storytelling; Formation of readers; Contação de histórias; CELLIJ; Formação de leitores